Korean Drama and Youth Imitation Behavior: A Case Study on Pekanbaru Students - Imron Rosidi; Masduki Masduki; Vivi Aulia Agus (Besari: Journal of Social and Cultural Studies, 2024)
Technological advances and the development of globalization have led to the growth of global and regional media which ultimately encouraged the emergence of K-Pop culture in Indonesia. The purpose of this study was to determine the influence of watching Korean dramas on the imitation behavior of Pekanbaru students. The theory used is the S-O-R (Stimulus, Organism and Response) theory to explain the data and analysis of the stages of students' imitation behavior towards Korean dramas. The research methodology used is a descriptive qualitative method reinforced by interview data sources with references in the form of relevant articles. The research informants used were students of Pekanbaru Telecommunication Middle School, which were determined through purposive sampling techniques. The results of the study showed that based on the analysis of the SOR theory carried out, there were behaviors that were imitated by Pekanbaru Telecommunication Middle School students from the Korean dramas they watched. The habits imitated by Pekanbaru students were related to fashion, including makeup and skin care, eating habits, and language style or terms in Korean.